The relationship between blood pressure and risk of fall of the elderly in Kelating Village, Tabanan, Bali - Dewa Ayu Ketut Indriani Putri; Desak Made Wahyu Ariningsih; Govinda Vittala; Made Hendra Satria Nugraha (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Increasing the age of the elderly will cause a decrease in body functions. One is a decreased cardiovascular function, triggering cardiovascular disorders such as increased blood pressure. Increased blood pressure in the elderly can affect postural balance, so that it can cause an increase in the risk of falls in the elderly. Methods: The study used a cross-sectional analytic design. This study was conducted on May 22, 2022. The sample in this study was selected using a simple random sampling technique. The number of samples in this study was 78 people. The data was analyzed using the SPSS software, which was divided into three parts, namely univariate analysis to describe the frequency distribution of each variable, normality test to determine whether the distribution of data was normally distributed or not where the normality test used the KoImogrov-Smirnov test and bivariate analysis to determine the relationship between the two variables analysis method used Spearman's Rho test. Results: The relationship between systolic blood pressure and risk of fall was p=0.000 and r=0.866, while the relationship between diastolic blood pressure and risk of fall was p=0.000 and r=0.520. Conclusion: This study concludes that there was a relationship between blood pressure and the risk of falls in the elderly in Kelating Village.